Detection of anti-SARS-CoV-2-Spike/RBD antibodies in vaccinated elderly from residential care facilities in Romania, April 2021 - Vremera, Teodora; Furtunescu, Florentina Ligia; Leustean, Mihaela; Rafila, Alexandru; David, Adina; Radu, Iuliana; Cornienco, Ana Maria; Gatea, Adina; Ilie, Ciprian; Iancu, Luminita Smaranda; Pistol, Adriana (Frontiers in Epidemiology, 2022)
Introduction SARS-CoV-2 infection rates and related mortality in elderly from residential care facilities are high. The aim of this study was to explore the immune status after COVID-19 vaccination in people 65 years and older. Methods The study involved volunteer participants living in residential care facilities. The level of anti-Spike/RBD antibodies was measured at 2–12 weeks after complete vaccination, using chemiluminescent microparticle immunoassay (SARS-CoV-2 IgG II Quant Abbott). Results We have analyzed 635 serum samples collected from volunteers living in 21 Residential Care Facilities. With one exception, in which the vaccination was done with the Moderna vaccine, all volunteers received the Pfizer-Comirnaty vaccine. Individuals enrolled in the study had ages between 65–110 years (median 79 years). Of the people tested, 54.8% reported at least one comorbidity and 59.2% reported having had COVID-19 before vaccination. The presence of anti-S/RBD antibodies at a protective level was detected in 98.7% of those tested (n = 627 persons) with a wide variation of antibody levels, from 7.1 to 5,680 BAU/ml (median 1287 BAU/ml). Antibody levels appeared to be significantly correlated to previous infection (r = 0.302, p = 0.000). Conclusions The study revealed the presence of anti-SARS CoV-2 antibodies in a significant percentage of those tested (98.7%). Of these, more than half had high antibody levels. Pre-vaccination COVID-19 was the only factor found to be associated with higher anti-S/RBD levels. The significant response in elderly people, even in those with comorbidities, supports the vaccination measure for this category, irrespective of associated disabilities or previous infection.